Microscopic diffusion properties of fixed breast tissue: Preliminary findings. Issue 6 (17th December 2014) - Norddin, Narina; Power, Carl; Watson, Geoffrey; Cowin, Gary; Kurniawan, Nyoman D.; Gluch, Laurence; Bourne, Roger M.
Abstract : Purpose: To investigate the microscopic diffusion properties of formalin‐fixed breast tissue. Methods: Diffusion microimaging was performed at 16.4T with 40‐μm isotropic voxels on two normal and two cancer tissue samples from four patients. Results were correlated with histology of the samples. Results: Diffusion‐weighted images and mean diffusivity maps demonstrated distinct diffusivity differences between breast tissue components. Mean diffusivity (MD) in normal tissue was 0.59 ± 0.24 μm 2 /ms for gland lobule (voxels containing epithelium and intralobular stroma) and 1.23 ± 0.34 μm 2 /ms for interlobular fibrous stroma. In the cancer samples, MD = 0.45 ± 0.23 μm 2 /ms for invasive ductal carcinoma (voxels contain epithelium and intralobular stroma) and 0.61 ± 0.35 μm 2 /ms for ductal carcinoma in situ. There were significant MD differences between all tissue components ( P < 0.005), except between gland lobule and ductal carcinoma in situ ( P = 0.71). The low diffusivity of epithelium‐rich cancer tissue and of normal epithelium relative to its supporting fibrous stroma was similar to that reported for prostate tissue and the esophageal wall. Conclusion: Diffusion microimaging demonstrates distinct diffusivity differences between breast tissue glandular structures. Low diffusivity may be a distinctive feature of mammalian epithelia. Magn Reson Med 74:1733–1739, 2015. © 2014 Wiley Periodicals, Inc.